ChemInform Abstract: Substituent‐Controlled Chemoselective Cleavage of C=C or C(sp2)—C(CO) Bond in α, β‐Unsaturated Carbonyl Compounds with H‐Phosphonates Leading to β‐Ketophosphonates. Issue 30 (July 2016) - Zhou, Yao; Rao, Changqing; Mai, Shaoyu; Song, Qiuling
Abstract: β‐Ketophosphonates are obtained via retro‐HWE reaction from α, β‐unsaturated carbonyl compounds and H‐phosphonates.